A RELAÇÃO DA POPULAÇÃO DE PANAMBI-RS COM O RIO FIÚZA - Bueno, Moacir Rudimar; Nishijima, Toshio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This work had the general objective to investigate the relationship of the population of Panambiwith the Rio Fiúza, the importance they give to the river and water. With the specific objectivesthere were researched the environmental aggressions to the river, identifying pollutants andconsequences of this pollution. We delimited the research from the bridge of BR 158 to theBridge of Avenida Conrad Adenauer. We sought a theoretical referential on the importance of thewater for the living beings and the diseases caused by the pollution and we conducted a fieldwork with pictures of the researched area. We complemented the study with a qualitativeresearch where the respondents were students and teachers of the eighth grade of the EnsinoFundamental at the Escola Estadual de Ensino Médio Pindorama, who through aquestionnaire said what they think about Rio Fiúza. The study revealed that the way of landuse, urban settlements, poor management of risk areas, lack of sewage treatment, destination ofwaste and little environmental education have contributed to the pollution of the river, as well asincreased the effects of flooding in the wetlands, which has weakened and left thepopulation exposed to serious health risks. The environmental education points to the importance of controlling the pollution of the Rio Fiúza, since this is the main source of water supply to thepopulation.